Colour, Light, and Materiality: Biophilic Interior Design Presence in Research and Practice - McGee, Beth; Park, Nam-Kyu (UI Scholars Hub, 2022)
The biophilic design hypothesis uses nature-based environmental design for optimising people’s health and well-being. Stephen Kellert in 2008 developed a list of biophilic attributes that was further refined in the Biophilic Interior Design Matrix (BID-M) to specifically support the interior application of biophilic design for health and well-being. The present study further investigates biophilic interior design using the BID-M language and the key interior design components colour, light, and materiality. The first part of the study reviewed four decades of literature related to biophilia and colour, light, and materiality to investigate a total of 19 publications. The second part of the study explored the perceptions of 23 design practitioners' and the use of biophilia related to colour, light, and materiality in their practice. For the first time, evidence was identified about colour, light, and materiality being linked to biophilic design and the attributes in the BID-M. The study results showed colour preferences were the most frequently identified theme, and practitioners used a variety of biophilic attributes in their practice. The top attributes shared by both the literature review and practitioners were the abstraction of nature, composition, natural light, and natural materials. This finding shows that there is a focus on biophilic attributes in both research and practice, however, there are still many attributes that have not been linked to research and are not being used in practice. Further inquiry is needed to better understand how biophilic design can be more diversely integrated for optimal nature-like interior environments.